2021
DOI: 10.1038/s41598-021-82255-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of relative social rank within a social hierarchy on neural activation in response to familiar or unfamiliar social signals

Abstract: Competent social functioning of group-living species relies on the ability of individuals to detect and utilize conspecific social cues to guide behavior. Previous studies have identified numerous brain regions involved in processing these external cues, collectively referred to as the Social Decision-Making Network. However, how the brain encodes social information with respect to an individual’s social status has not been thoroughly examined. In mice, cues about an individual’s identity, including social sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…In male mice ( Mus musculus ), specific receptors in the VNO have been identified as necessary for sex cue discrimination and expression of sexual and aggressive behaviour [ 26 , 27 ]. In both female and male mice, downstream targets of the VNO exhibit greater activation upon sniffing urine from dominant males compared to urine from subordinate males, as evidenced by number of cfos immunoreactive cells, a proxy of neuronal excitation [ 28 , 29 ]. This activity could represent the detection of higher levels of major urinary proteins (MUPs), some of which are crucial for territory marking [ 30 ].…”
Section: Representation Of Status Signalsmentioning
confidence: 99%
See 3 more Smart Citations
“…In male mice ( Mus musculus ), specific receptors in the VNO have been identified as necessary for sex cue discrimination and expression of sexual and aggressive behaviour [ 26 , 27 ]. In both female and male mice, downstream targets of the VNO exhibit greater activation upon sniffing urine from dominant males compared to urine from subordinate males, as evidenced by number of cfos immunoreactive cells, a proxy of neuronal excitation [ 28 , 29 ]. This activity could represent the detection of higher levels of major urinary proteins (MUPs), some of which are crucial for territory marking [ 30 ].…”
Section: Representation Of Status Signalsmentioning
confidence: 99%
“…Interestingly, in male mice, the MeA has more neurons with cfos immunoreactivity ( cfos -ir) after subjects are exposed to urine from an alpha (i.e. the most dominant individual in a hierarchy) compared to a subordinate conspecific, and this does not depend on the subject's own social rank or their familiarity with the cue source, although these factors may influence the biological relevance of the cue [ 29 ]. Activity in the MeA is also increased in both dominant and subordinate greater long-tailed hamsters ( Tscheskia triton ) following agonistic encounters and is not correlated to expression of aggression or defensive behaviour [ 42 ].…”
Section: Representation Of Status Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of our knowledge of the MeA comes from rodent work, which has shown that it is involved in a wide range of social behaviors (Lehman et al, 1980 ; Haller, 2018 ), and is a major constituent of the accessory olfactory system, receiving the bulk of monosynaptic projections from the accessory olfactory bulb (Mohedano-Moriano et al, 2007 ; Pro-Sistiaga et al, 2007 ). Within the accessory olfactory system, the MeA plays an important role in processing pheromonal signals and differentiating olfactory social cues including those that carry meaning about sex, age, and danger status (Bergan et al, 2014 ; Li et al, 2017 ; Yao et al, 2017 ; Lee et al, 2021 ). Social behaviors in rodents are strongly impacted by the main olfactory system (Keshavarzi et al, 2015 ; Pardo-Bellver et al, 2017 ), so it is likely that the MeA is involved in the processing of social cues that are encountered through the main olfactory system as well.…”
Section: Section 1: Literature Review Of the Mea Coa And Pacmentioning
confidence: 99%